Study on Properties of Branched Hydrophobically Modified Polyacrylamide for Polymer Flooding - Lei-Ting Shi; Cheng Li; Shan-Shan Zhu; Jie Xu; Bao-Zong Sun; Zhong-Bin Ye (Journal of Chemistry)
The effect of partially hydrolyzed polyacrylamides (HPAMs) used for polymer flooding is unsatisfactory under the conditions of high temperature and high salinity. In order to improve the viscosifying ability of HPAM, branched macromolecular skeleton monomer is used to change the linear backbone structure. A new branched hydrophobically modified polyacrylamide (BHMPAM) was synthesized by the free radical copolymerization of functionalized branched macromolecular skeleton monomer, acrylamide (AM), acrylic acid (AA), and hydrophobic monomer hexadecyl-allyl-dimethyl ammonium chloride (C16DMAAC). The properties of polymer solution were characterized; the results of the experiments showed that BHMPAM exhibited the properties of pseudoplastic fluid, and the viscosity of BHMPAM was 345.9 mPa·s (polymer concentration was 1750 mg/L) under the condition of 75°C and 9374 mg/L of salinity. Moreover, BHMPAM also performed well in viscoelasticity which can meet the property requirements for EOR polymer.